2008
DOI: 10.1509/jmkr.45.6.731
|View full text |Cite
|
Sign up to set email alerts
|

Circles, Squares, and Choice: The Effect of Shape Arrays on Uniqueness and Variety Seeking

Abstract: Five experiments demonstrate that exposure to novel visual stimulus arrays of geometric shapes affects consumers' real choices among products. The authors first demonstrate that exposure to variety arrays (arrays of differing shapes) increases variety seeking (Study 1). They then show that exposure to uniqueness arrays (e.g., one circle among six squares) increases choice of unique over common objects (Studies 2 and 3) and interacts with chronic need for uniqueness (Study 3). In the final two studies, the auth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
78
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(89 citation statements)
references
References 27 publications
8
78
0
3
Order By: Relevance
“…Next, we primed half the participants with uniqueness (adapted from Maimaran and Wheeler 2008). These individuals were asked to look at eight pictures and identify the number of circles and squares in each image.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Next, we primed half the participants with uniqueness (adapted from Maimaran and Wheeler 2008). These individuals were asked to look at eight pictures and identify the number of circles and squares in each image.…”
Section: Methodsmentioning
confidence: 99%
“…Each picture contained an array of shapes in which all the shapes were the same except one (e.g., ⅪyⅪⅪⅪⅪⅪⅪⅪⅪ). Exposure to such figures has been shown to increase uniqueness seeking behavior by making uniqueness motives more accessible (Maimaran and Wheeler 2008). Control participants did not complete the priming task.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our experimental approach, using a web-based simulated shopping environment (Lo, 2009;Lo & Harvey, 2011;Maimaran & Wheeler, 2008), 2 enabled us to investigate the decision processes underlying compulsive buying.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, consistency should result in familiarity. In line with this, Maimaran and Wheeler (2008) demonstrated that simply exposing consumers to novel geometric shapes could evoke variety seeking, whereas a homogenous array of shapes prompts consistency seeking. Thus, consumers may seek consistency for liking while they also seek variety for interest.…”
Section: Consumers As Consistency Seekers and Variety Seekersmentioning
confidence: 56%